Distance: A Moderator Between Walking Activity and Pattern Classification - Ching Yee Yong; Kim Mey Chew; Rubita Sudirman; Nasrul Humaimi Mahmood (Institute of Advanced Engineering and Science, 2012)
The research of this paper is to investigate does distance will affecting the walking activity and the pattern for classification. This paper built a comprehensive picture of the human walking activity, programming language, workflow of the tool, features extraction and patterns classification method and captured the attitudes of the respondents. The subject was performed a range of walking activity in a controlled laboratory setting. The result of this study shows that the moderating effects of walking distance explains 15.80% (Gyroscope), 74.60% (Accelerometer) and 98.60% (Compass) of variance in research output. The result is expected to be beneficial and able to assist researchers and medical officers in analyzing human motion and its pattern classification.